Genus Cistus: a model for exploring labdane-type diterpenes' biosynthesis and a natural source of high value products with biological, aromatic, and pharmacological properties - Papaefthimiou, Dimitra; Papanikolaou, Antigoni; Falara, Vasiliki; Givanoudi, Stella; Kostas, Stefanos; Kanellis, Angelos K. (Frontiers in Chemistry, 2014)
The family Cistaceae (Angiosperm, Malvales) consists of 8 genera and 180 species, with 5 genera native to the Mediterranean area (Cistus, Fumara, Halimium, Helianthemum, and Tuberaria). Traditionally, a number of Cistus species have been used in Mediterranean folk medicine as herbal tea infusions for healing digestive problems and colds, as extracts for the treatment of diseases, and as fragrances. The resin, ladano, secreted by the glandular trichomes of certain Cistus species contains a number of phytochemicals with antioxidant, antibacterial, antifungal, and anticancer properties. Furthermore, total leaf aqueous extracts possess anti-influenza virus activity. All these properties have been attributed to phytochemicals such as terpenoids, including diterpenes, labdane-type diterpenes and clerodanes, phenylpropanoids, including flavonoids and ellagitannins, several groups of alkaloids and other types of secondary metabolites. In the past 20 years, research on Cistus involved chemical, biological and phylogenetic analyses but recent investigations have involved genomic and molecular approaches. Our lab is exploring the biosynthetic machinery that generates terpenoids and phenylpropanoids, with a goal to harness their numerous properties that have applications in the pharmaceutical, chemical and aromatic industries. This review focuses on the systematics, botanical characteristics, geographic distribution, chemical analyses, biological function and biosynthesis of major compounds, as well as genomic analyses and biotechnological approaches of the main Cistus species found in the Mediterranean basin, namely C. albidus, C. creticus, C. crispus, C. parviflorus, C. monspeliensis, C. populifolius, C. salviifolius, C. ladanifer, C. laurifolius, and C. clusii.